Metaphysics of Freedom? Kant's Concept of Cosmological Freedom in Historical and Systematic Perspective. - Christian H. Krijnen (Editor) (Critical Studies in German Idealism, 2018)
Freedom is one of the main issues of modern philosophy and Kant's philosophy of freedom a major source for comprehending it. Whereas in contemporary debates Kant's concept of practical freedom is addressed frequently, the cosmological foundation of it is much less discussed and even mostly taken for granted. In Metaphysics of Freedom? , by contrast, Kant's concept of cosmological freedom is scrutinized both in a historical and a systematic perspective. As a result, a deeper and broader understanding of Kant's conception of freedom, its presuppositions, and problems emerges.